On Conspiracy Thinking: Conspiracist Ideology as a Modern Phenomenon - Stefan Christoph (Politics and Governance, 2022)
Conspiracism is a well‐known topos in the history of humankind. Cassius Dio wrote about it as did anti‐Judaic authors in the Middle Ages. Nevertheless, from the dawn of modernity until today, we have faced the rise of a new phenomenon. Pretty much on the eve of the French Revolution, conspiracists began to tell anti‐Catholic and anti‐masonic narratives down to the last detail. Jews, later on, became a recurring foe in those anti‐modernist narratives. Conspiracism managed successfully to incorporate other forms of anti‐modernism to form a fairly new form of thinking that I call “conspiracist ideology.” While Enlightenment was the setting in which this amalgamation could take place, conspiracist ideology and its intellectual roots were characterized by a deep rejection of enlightenment thinking. The dialectical nature of conspiracist ideology is what makes it interesting from a historical perspective, in particular for the history of ideas.